Perlindungan Hak Cipta Dalam Perspektif Asas Kebebasan Berkontrak - Yulisti, Prayogi; Yetniwati, Yetniwati; Hasan, Umar (Magister Kenotariatan, Universitas Jambi, 2024)
This study aims to examine how copyright buyers are protected in sold flat sale and purchase agreements after the publication of Article 18 of the Copyright Law number 28 of 2014, where the agreement expires after 25 years. Does the sale and purchase agreement remain valid according to the Civil Code so that the copyright buyer still gets the exclusive commercial rights. As well as how the perspective of a sold flat agreement is seen from the validity and protection of copyright buyers This research is a legal research that examines the perspective of laws related to sold flat agreements descriptively.